Seminal papers in spinal surgery. Issue 4 (August 2018) - Nash, William; Walker, Roland; Lucas, Jonathan; Ajuied, Adil
Abstract: Evidence based medicine should underpin the practice of all orthopaedic surgeons. Spinal pathology should be considered in the differential diagnosis for pain in every upper and lower limbs region and an understanding of spinal anatomy and physiology is vital in the management of the trauma patient. We present ten key articles, which have been selected for their impact within the field. They encompass trauma, degenerative, inflammatory, deformity and emergency spinal disorders. The articles range from level I randomized control trials to level V expert opinion. An understanding of their methodology and key findings should be part of the core knowledge encompassing spinal surgery and will, in particular, be of benefit for those preparing for final professional examinations.